2020
DOI: 10.1111/acem.14132
|View full text |Cite
|
Sign up to set email alerts
|

Child Protection Team Consultation for Injuries Potentially Due to Child Abuse in Community Emergency Departments

Abstract: Objectives Emergency care for children is provided predominantly in community emergency departments (CEDs), where abusive injuries frequently go unrecognized. Increasing access to regional child abuse experts may improve detection of abuse in CEDs. In three CEDs, we intervened to increase involvement of a regional hospital child protection team (CPT) for injuries associated with abuse in children < 12 months old. We aimed to increase CPT consultations about these infants from the 3% baseline to an average of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Other studies on improving NAT evaluations focused on specific elements, such as a skeletal survey [33][34][35] or child abuse specialist consultation. 27,32 Some published interventions relied on the EHR to aid in detecting abuse concerns 28,30 or patient screening tools. [19][20][21][22][23][24][25][26]29,31 One QI project improved NAT bundle adherence from 47% to 69% among 640 eligible patients <3 years old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies on improving NAT evaluations focused on specific elements, such as a skeletal survey [33][34][35] or child abuse specialist consultation. 27,32 Some published interventions relied on the EHR to aid in detecting abuse concerns 28,30 or patient screening tools. [19][20][21][22][23][24][25][26]29,31 One QI project improved NAT bundle adherence from 47% to 69% among 640 eligible patients <3 years old.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29][30][31] Other studies targeted specific aspects of the NAT workup, including increased consults to a hospital child protection team. 25,[32][33][34][35][36] One hospital developed pediatric emergency department (PED) NAT evaluation guidelines for patients <3 years old and observed modest improvement in provider adherence. 37 In contrast, our project implemented a multidisciplinary, hospital-wide suspected NAT clinical guideline based on AAP recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…This uncertainty might explain the low reporting rate among health professionals. Other studies have shown that the absence of clear guidelines and protocols for detecting and reporting child abuse can lead to reduced willingness to report and to a reduction in the accurate identification of child abuse cases (Ben Natan et al., 2012; Flaherty et al., 2004; Flaherty et al., 2008; Gunn et al., 2005; Piltz & Wachtel, 2009; Cleek et al., 2019; Tiyyagura et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of a child abuse pathway led to an increase in occult injury testing for at‐risk infants, reports to child protective services, and adherence to national child abuse evaluation guidelines. Providers who had consulted the child protection team reported that they valued confirmation from an expert even when the injury was thought to be non‐abusive, appreciated the concrete screening questions asked by the child protection team about the injury and social factors given that social work was not readily available, and appreciated the support and availability of the child protection team (Tiyyagura et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…showed that when Community emergency departments, referred cases to dedicated child protection team, on identifying any of the above-mentioned TEN-FACE-sp injuries, an increased reporting of child abuse occurred (from 10.7% to 32.6%). [ 29 ]…”
Section: Reporting Of Abuse and Role Of Doctors Teachers And Parentsmentioning
confidence: 99%